2011
DOI: 10.3892/or.2011.1278
|View full text |Cite
|
Sign up to set email alerts
|

Screening for serological biomarkers of pancreatic cancer by two-dimensional electrophoresis and liquid chromatography-tandem mass spectrometry

Abstract: Abstract. pancreatic cancer (pc) is one of the most lethal malignant tumors because of late diagnosis and the lack of response to various therapies. to identify potential biomarkers in cancerous serum from early stage pc patients, we carried out two-dimensional gel electrophoresis (2-De) and liquid chromatography-tandem mass spectrometry (lc-Ms/Ms) to compare the serum proteomic profiles from 45 patients with pc and 20 healthy volunteers. seven spots showed differential expression on 2-De gels and two up-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Seven protein spots were differentially expressed. Serum isoforms of alpha-1-antitrypsin (AAT), also confirmed by western blot, were described as upregulated and potential serum biomarkers for pancreatic cancer [90]. …”
Section: Mass Spectrometry: the Cancer Biomarker Discovery Toolmentioning
confidence: 99%
“…Seven protein spots were differentially expressed. Serum isoforms of alpha-1-antitrypsin (AAT), also confirmed by western blot, were described as upregulated and potential serum biomarkers for pancreatic cancer [90]. …”
Section: Mass Spectrometry: the Cancer Biomarker Discovery Toolmentioning
confidence: 99%
“…RCN1 has been demonstrated to be highly expressed in a variety of tumor cells and is correlated with patient prognosis in renal cell carcinoma, prostate cancer, glioblastoma, non-small cell lung cancer, oral squamous cell carcinoma, nasopharyngeal cancer, colon cancer, laryngeal cancer, highly aggressive breast cancer, sorafenib-resistant hepatocellular carcinoma cells, and gemcitabine-insensitive human pancreatic adenocarcinoma cells, among others [20][21][22]24,25,27,[55][56][57][58][59][60][61][62][63]. Yoshida et al [64] reported that RCN1 was expressed in lymphatic endothelial cells (T-LECs) and lung cancer cells in lung tumors, but not in lymphatic endothelial cells (N-LECs) in nontumor tissues.…”
Section: Discussionmentioning
confidence: 99%